Anal cancer screening among women with HIV: provider experiences and system-level challenges. Issue 2 (1st February 2022) - Higashi, Robin T.; Rodriguez, Serena A.; Betts, Andrea C.; Tiro, Jasmin A.; Luque, Amneris E.; Rivera, Rachel; Barnes, Arti
ABSTRACT: Women living with HIV (WLWH) are at increased risk of anal cancer compared to women without HIV, often due to persistent human papillomavirus (HPV) infections. This paper describes current practices and challenges conducting anal cancer screening for WLWH at an urban integrated safety-net system and a non-profit community-based HIV clinic. We conducted 25 semi-structured interviews with clinical and administrative stakeholders to assess knowledge, clinic practices and procedures, and experiences with anal cancer screening. Interview transcripts and fieldnotes were thematically analyzed using an iterative deductive and inductive coding scheme. Findings were organized by the Consolidated Framework for Implementation Research (CFIR) domains and constructs. Provider-level barriers to conducting anal cancer screening included limited knowledge of guidelines. System-level barriers included: structural characteristics such as lack of coordination between clinics to discern provider roles and responsibilities; and limitations in available resources such as configuration of electronic health records and infrastructure to manage referrals of abnormal anal Pap results. We conclude that anal cancer screening and follow-up for WLWH requires organization and coordination between multiple care teams, updated clinical information systems to facilitate communication and support anal Pap ordering and result documentation, and infrastructure that includes policies and protocols for management of abnormal results. Trial registration: ClinicalTrials.gov identifier: NCT02135419 .